2017
DOI: 10.1001/jamasurg.2016.5040
|View full text |Cite
|
Sign up to set email alerts
|

Association of Remnant Liver Ischemia With Early Recurrence and Poor Survival After Liver Resection in Patients With Hepatocellular Carcinoma

Abstract: Preventive management and technical refinements in hepatectomy are important to decrease the risk of RLI and to improve survival of patients with hepatocellular carcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
62
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 82 publications
(63 citation statements)
references
References 38 publications
0
62
1
Order By: Relevance
“…31,32 Some evidence shows that clamping is not insignificant. Cho et al 33 showed that the use of the Pringle maneuver and longer operative times were independent risk factors for severe remnant liver ischemia. Hao et al 34 suggested that intermittent portal clamping is an independent risk factor for poor long-term postoperative outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…31,32 Some evidence shows that clamping is not insignificant. Cho et al 33 showed that the use of the Pringle maneuver and longer operative times were independent risk factors for severe remnant liver ischemia. Hao et al 34 suggested that intermittent portal clamping is an independent risk factor for poor long-term postoperative outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…There are multiple risk factors for recurrence after HCC resection. In a prior report, the host factors for recurrence included hepatitis B or C; the tumor factors included vascular invasion, satellite nodule, tumor size, and advanced tumor stage; and surgical factors included the extent of resection, RM, perioperative transfusion, remnant liver ischemia after surgery, and postoperative complications [4, 20]. …”
Section: Discussionmentioning
confidence: 99%
“…Pringle was the first to advocate ligating the inflow vessels of the liver during transection of the parenchyma for bleeding reduction [ 17 , 18 ]. While ischemic damage is a major problem [ 19 , 20 ], ligation and division of the corresponding vessels and ducts via dissection of the hepatic hilus for blood loss reduction during hepatic parenchyma transection when performing right hepatectomy were first described by Lortat-Jacobs and Robert in 1952, which were known as anatomical hepatectomy or classical hepatectomy later [ 21 ]. However, the risk of hemorrhage during dissection and bile leaks occurring in the postoperative period makes this approach not suitable for laparoscopy.…”
Section: Discussionmentioning
confidence: 99%